Electrospinning of stimuli‐responsive polymers for controlled drug delivery: pH‐ and temperature‐driven release. Issue 5 (4th February 2022) - Williams, Leah; Hatton, Fiona L.; Willcock, Helen; Mele, Elisa
Abstract: Stimuli‐responsive polymers have attracted academic interest over the last 60 years due to their potential use in developing systems with a range of functionalities that can be activated by external artificial triggers. The diversity of responses and stimuli, which can be achieved through careful polymer selection and processing, opens up applications in nearly every sector. In particular, the use of responsive polymers for the controlled delivery of drugs and bioactive compounds has been heavily researched. This review provides an overview of the recent advancements in electrospinning of temperature‐ and pH‐responsive polymers to create networks of nanofibres with controlled drug delivery profiles for biomedical applications. Abstract : Stimuli‐responsive polymers hold the potential for use in developing systems with a diverse range of functionalities activated by external artificial triggers, and thus have attracted interest in nearly every sector. In particular, the use of responsive polymers for the controlled delivery of drugs and bioactive compounds has been heavily researched. This review gives an overview of the recent advancements in electrospinning of temperature‐ and pH‐responsive polymers to create networks of nanofibres with controlled drug delivery profiles for biomedical applications.